A qualitative study on mental health and wellbeing of Syrian refugees in the UK. (30th September 2020) - Tattan, M; Paudyal, P; Cooper, M
Abstract: Background: The Syrian conflict has resulted in an estimated 5.3 million registered Syrian refugees in various parts of the world. Evidence suggests that these individuals are at considerable risk of developing common mental disorders. This study aimed to explore the mental wellbeing of Syrian refugees, identify their coping mechanisms and pathways towards integration into new communities, and formulate recommendations for better access to mental healthcare services. Methods: We conducted a qualitative study using in-depth semi-structured interviews with adult refugees (>18 years old) who are currently residing in Southeast of England. Interviews were conducted in Arabic, recorded, transcribed and translated verbatim. Translated transcripts were analysed using thematic analysis. Ethical Approval was obtained from the Brighton and Sussex Medical School Research Governance Ethics Committee (ER/BSMS9DAP/1). Results: Twelve participants (3 females and 9 males) took part in the study; all were born in Syria and the majority (n = 9) were over 45 years of age. Participants described symptoms of reduced psychological wellbeing. Preliminary findings shows that almost all participants talked about psychological distress resulting from previous trauma, loss of and separation from family members and challenges adjusting to their host country. Barriers to accessing the healthcare system in the UK included fear of stigma, being misunderstood by healthcare staff and language issues. Communicating with loved ones, connecting with nature, practising faith and pursuing hobbies were reported as coping strategies. Conclusions: For Syrian refugees in the UK, mental wellbeing embraces living with past traumatic experiences, achieving social integration and facing challenges accessing healthcare. Understanding differences between refugee and host communities is key to appropriately cater to the specific needs of each community and achieve equity in healthcare access. Key messages: Syrian refugees in UK described symptoms of reduced psychological wellbeing. Understanding the needs of refugee communities is necessary to achieve equity in healthcare access.